TRH1 encodes a potassium transporter required for tip growth in Arabidopsis root hairs. - Rigas, S; Debrosses, G; Haralampidis, K; Vicente-Agullo, F; Feldmann, K; Grabov, A; Dolan, L; Hatzopoulos, P (2001)
Root hair initiation involves the formation of a bulge at the basal end of the trichoblast by localized diffuse growth. Tip growth occurs subsequently at this initiation site and is accompanied by the establishment of a polarized cytoplasmic organization. Arabidopsis plants homozygous for a complete loss-of-function tiny root hair 1 (trh1) mutation were generated by means of the T-DNA-tagging method. Trichoblasts of trh1 plants form initiation sites but fail to undergo tip growth. A predicted primary structure of TRH1 indicates that it belongs to the AtKT/AtKUP/HAK K(+) transporter family. The proposed function of TRH1 as a K(+) transporter was confirmed in (86)Rb uptake experiments, which demonstrated that trh1 plants are partially impaired in K(+) transport. In line with these results, TRH1 was able to complement the trk1 potassium transporter mutant of Saccharomyces, which is defective in high-affinity K(+) uptake. Surprisingly, the trh1 phenotype was not restored when mutant seedlings were grown at high external potassium concentrations. These data demonstrate that TRH1 mediates K(+) transport in Arabidopsis roots and is responsible for specific K(+) translocation, which is essential for root hair elongation.